Seyahat acentalarında muhasebe sistemi - Özdemir, Gülser (My University, 2009)
Turizme olan ilginin artması bir çok sektörü olumlu yönde etkilemektedir. Bu etkileşimden en çok pay alan seyahat acentalarıdır. Seyahat acentaları bu sektörün yapı taşlarını oluşturmaktadır. Bu işletmeler turizmde bir dağıtım aracı olarak turistik ürünlerin satışını yapmaktadırlar. Satmış oldukları bu hizmetlerden elde ettikleri gelirlerin, katlandıkları maliyetlerin muhasebe uygulamalarını Tek Düzen Muhasebe Sistemi Hesap Planı ve Kayıt Düzenine göre yürütmektedirler. Seyahat Acentaları, Seyahat Acentalarında Muhasebe Kayıtları.

Some sectors in economy are affected positively from inceasing of attactiveness of the tourism sector. Travel agencies are more affected organizations from this interaction. Travel agencies are corner stone and important part of the tourism sector. These institutions have sold and marketed the touristics products and services as a being distribution chain. As a result of these functionings they have got operating expenses and revenues. Travel agencies implement Turkish Uniform Accounting System for accounting records and application of these operating revenues and costs. Key Words: Travel Agencies, Acounting Systems of the Travel Agencies.
Keywords: Muhasebe; Seyahat Acentaları